PENGARUH GOOD CORPORATE GOVERNANCE, SALES GROWTH DAN FIRM SIZE TERHADAP KINERJA KEUANGAN - Laksmanta, Ananda Mitsa Ghalizha; Rachmawati, Titiek (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to analyze the effect of good corporate governance, sales growth and firm size on financial performance. The population of this study is Heavy Construction and Civil Engineering companies listed on IDX in 2018-2021 totaling 25 companies. The way of collecting data is using document study and the sampling is using purposive sampling. Based on the result of hypothesis testing on good corporate governance, the original sample value (O) is 0.022 with a t-statistic value of 0.148 < 1.96 and p-values of 0.882 > 0.05. These result indicate that H1 is rejected because good corporate governance has no significant effect on financial performance. The result of the sales growth test show that the original sample value (O) is 0.525 with a t-statistic value of 3.123 > 1.96 and a p-value of 0.002 < 0.05. These result indicate that H2 is accepted because sales growth has a significant positive effect on financial performance. Meanwhile, for firm size, the original sample value (O) is -0.442 with a t-statistic value of 3.867 > 1.96 and p-value of 0.000 < 0.05. These result indicate that H3 is accepted because firm size has a significant negative effect on financial performance.